Translational Control under Stress: Reshaping the Translatome - Advani, Vivek M.; Ivanov, Pavel (BioEssays, 2019)
Adequate reprogramming of cellular metabolism in response to stresses or suboptimal growth conditions involves a myriad of coordinated changes that serve to promote cell survival. As protein synthesis is an energetically expensive process, its regulation under stress is of critical importance. Reprogramming of messenger RNA (mRNA) translation involves well‐understood stress‐activated kinases that target components of translation initiation machinery, resulting in the robust inhibition of general translation and promotion of the translation of stress‐responsive proteins. Translational arrest of mRNAs also results in the accumulation of transcripts in cytoplasmic foci called stress granules. Recent studies focus on the key roles of transfer RNA (tRNA) in stress‐induced translational reprogramming. These include stress‐specific regulation of tRNA pools, codon‐biased translation influenced by tRNA modifications, tRNA miscoding, and tRNA cleavage. In combination, signal transduction pathways and tRNA metabolism changes regulate translation during stress, resulting in adaptation and cell survival. This review examines molecular mechanisms that regulate protein synthesis in response to stress. Translational control contributes to various aspects of cell homeostasis. As messenger RNA (mRNA) translation is energy‐expensive, its regulation is critical. Reprogramming of mRNA translation during stress involves signal transduction pathways and transfer RNA metabolism changes that aim at cell survival. This review examines molecular mechanisms that regulate protein synthesis in response to stress.